[Silent screams ; Breaking the silence ; Lahat para sa lahar [videorecording] - Lazaro, Cheche (Quezon City Probe Productions, 1992)
A study by a group of University of the Philippines psychologists on the extent of torture of political detainees. Also includes interviews with the detainees about their physical and mental tortures. A woman's group takes a look at cases of domestic violence - battered wives. A musical presentations of famous singers and musicians giving their concert earnings to Pinatubo victims.
Silent screams (22 min.) -- Breaking the silence (14 min.) -- Lahat para sa lahar (15 min.)
VHS.
Keywords: Political prisoners -- Philippines; Abused wives -- Philippines; Conjugal violence -- Philippines; Family violence -- Philippines; Music -- Performance. -- Philippines